Psychology applied to teaching - Snowman, Jack.; Biehler, Robert (Boston : Houghton Mifflin, 2000)
Applying psychology to teaching. Stage theories of development. Age-level characteristics. Understanding student differences. Addressing cultural and socioeconomic diversity. Accommodating student variability...
Keywords: Education; Educational psychology; Educational psychology